Identificação de plantas utilizadas como medicinais e levantamento florístico e fitossociológico e em áreas de fundo de pasto no município de Curaçá - Bahia - Jesus, Camila Gonzaga de (2013)
This study aimed to characterize the structure of plant communities, the impact caused by human action in these species and identify areas in which the fund pasture medicinal plants used by the people, through forms previously prepared and subsequent collection of plants cited in two Communities Fundo de Pasto in Village of São Bento and Patamuté, Curaçá-Bahia. To phytosociological analysis method was used to point quadrant in 10 transects of 200 m with points spaced 20 to 20 m. We sampled all individuals shrubs and trees that had greater than 1.30 m height and diameter at ground height greater than or equal to 0.3 cm. The analysis was performed using the program Fitpoac1. We carried out a comparative analysis of floristic similarity and evaluation of the diameter distribution was calculated where the quotient “q” to verify that the study area is balanced. The interviews were conducted in a semi-structured, for location and collection of plants was performed non-probability sampling intentional, which can be used to describe phenomena, data and generate hypotheses, using the technique “snowball”. The analysis revealed a set phytosociological floristic represented by 11 families, 24 genera and 28 species. In São BentoSt. Benedict (SB) were recorded 07 families and 16 species. In Patamuté (PT) enrolled 10 families and 22 species. The Shannon diversity index was 1.62 and 2.1 in SB PT. The most abundant species common to both fragments of study is Poincianella laxiflora (Tul.) L. P. Queiroz. Cluster analysis showed that the factor of geographical proximity and human action defined the separation of the three groups formed the similarity dendrogram. For the identification of the species as medicinal interviewed 25 people, 14 men and 11 women. The Community of São Bento were interviewed 12 people, aged between 30 and 87 years, with 50% of respondents had more than 60 years, the Community of Patamuté 13 people were interviewed between 35 and 96 years. Informants identified uses for 38 species and 25 SB in PT, belonging to 15 plant families. The maximum use values obtained were 1.33 and 0.77 Myracrodruon. urundeuva Allemão (aroeira) in SB, Libidibia ferrea (Mart. Ex Tul.) LP Queiroz (pau-ferro) in PT. Both species have medicinal use for inflammatory conditions. The use value average 0.38 and 0.23 in Sb and PT respectively. Regarding the frequency of citation of the use of the species in the SB Aroeira was the species most frequently mentioned by informants. In PT the ironwood was the most cited (13%). Regarding the various uses mentioned by informants communities study, treatments of conditions such as abdominal pain, flu, inflammation, kidney pain and healing were the most frequent. The study area has not provided a reason absolutely balanced, having mortality rates and growth variables, confirming the result of the strong anthropic generated by communities of bottom grazing. The results demonstrate that traditional knowledge of communities of bottom grazing areas studied might contribute significantly to the bioprospecting research to be conducted with plants of the caatinga serving as the basis for future pharmacological research and that species of lesser importance value, (Spondias tuberosa Arruda, Anadenanthera colubrina (Vell.) Brenan, Ziziphus joazeiro Mart., Myracrodruon urundeuva, Schinopsis brasiliensis Engl., Commiphora leptophloeos (Mart.) J.B.Gillett, Pseudobombax simplicifolium A. Robyns, Aspidosperma pyrifolium Mart., Jatropha multabilis (Pohl) Baill., Melochia tomentosa L., Sideroxylon obtusifolium (Roem. & Schult) e Mimosa tenuiflora (Willd.) Poir.) should be used for seedling production and recovery of bottom grazing areas studied.